Sesja II - Współczesna terapia chorób układu oddechowegoAntibiotic therapy of pneumonia - Dworacka, Marzena (Przewodnik Lekarza/Guide for GPs Supplement, 2008)
Antibiotic therapy in respiratory infections, especially treatment of pneumonia, is mostly empiric. Therefore many factors, apart from the antimicrobial spectrum, including factors modifying pharmacokinetic properties of antibiotics, co-existing diseases, and diet, should be considered. Interactions between antibiotics and another agents could also be the reason for unsuccessful treatment. Proper antibiotic combinations and avoidance of the most frequent therapeutic errors should be emphasized.